Seasonal influenza vaccine dose distribution in 195 countries (2004–2013): Little progress in estimated global vaccination coverage. Issue 42 (13th October 2015) - Palache, Abraham; Oriol-Mathieu, Valerie; Fino, Mireli; Xydia-Charmanta, Margarita; Influenza Vaccine Supply task force (IFPMA IVS)
Highlights Influenza vaccine dose distribution was assessed as a proxy for vaccine utilization. Distribution increased 87% between 2004 and 2013, but only 12% between 2008 and 2013. Seasonal influenza vaccination coverage rates remain well below recommended targets. Vaccination coverage targets are not being met under current vaccine recommendations. New policy measures are required to achieve greater benefits from influenza vaccines.